Mexico is criminalizing land, territory and environmental defenders - Amnesty International (Amnesty International, 2023)
The disproportionate use of criminal law is one of the main threats facing the right to protest peacefully in defense of land, territory and environment in Mexico, Amnesty International said today upon publishing a new report. Mexico: Land and Freedom? Criminalizing defenders of land, territory and environment documents the disproportionate use of the justice system to deter, punish and prevent defenders from protesting in demand of their rights.
Keywords: 2023-09 September; Chilón; Colonia Maya; Land Defenders; Sitilpech; Zacatepec

100 people executed as authorities continue relentless ‘killing spree’ - Amnesty International (Amnesty International, 2023)
Responding to the news that Saudi Arabia has already executed 100 people this year, Heba Morayef, Amnesty International’s Middle East and North Africa Director, said: “In clear contrast to Saudi Arabia’s repeated promises to limit its use of the death penalty, the Saudi authorities have already executed 100 people this year, revealing their chilling disregard for the right to life.
Keywords: 2023-09 September

What happened to Mahsa/Zhina Amini? - Amnesty International (Amnesty International, 2023)
In September 2022 Mahsa/Zhina Amini, a young woman from Iran’s oppressed Kurdish minority, visited Tehran with her brother. She was stopped and arrested by Iran’s “morality” police (gasht-e ershad), who routinely arbitrarily detain women who do not comply with the country’s abusive and discriminatory compulsory veiling laws.
Keywords: 2023-09 September

Arrest and detention of human rights lawyers an attack on the legal profession - Amnesty International (Amnesty International, 2023)
Amnesty International strongly condemns the arrest and detention of human rights lawyers simply for discharging their functions.
Keywords: 2023-09 September; Government